(untitled) (European Journal of Education and Psychology, 2018)
PSICO-A is a computer system for learning Psychology. It is specially designed for secondary school children. It is the first system in Psychology designed for learning didactic units of the subject. PSICO-A is based on many pedagogical influences, such as concept maps, free retrieval practice, effective feedback, simulations, digital games, and metacognition. A significant improvement has been shown in the conceptual performance in those children that constructed computer-generated maps using the system compared to those that have drawn them by hand. An evaluation was also made of the interactions between concept mapping and simulations, demonstrating that the first group of pupils performed better in simulations than the second group. Further studies are needed to study the influence of these two conditions of concept mapping on the performance of digital games.